2002
DOI: 10.1079/phn2002407
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of dietary patterns observed in the European Prospective Investigation into Cancer and Nutrition (EPIC) project

Abstract: Objective: To describe the diversity in dietary patterns existing across centres/regions participating in the European Prospective Investigation into Cancer and Nutrition (EPIC). Design and setting: Single 24-hour dietary recall measurements were obtained by means of standardised face-to-face interviews using the EPIC-SOFT software. These have been used to present a graphic multi-dimensional comparison of the adjusted mean consumption of 22 food groups. Subjects: In total, 35 955 men and women, aged 35-74 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
209
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(228 citation statements)
references
References 57 publications
15
209
2
2
Order By: Relevance
“…Our results suggest that a decrease in saturated fat should be recommended in the Catalan population. However, the 12% of energy derived from SFA found in the present study is still lower than the percentage found in other European populations (Slimani et al, 2002;Capita and Alonso-Calleja, 2003;Waijers et al, 2006) even in the Mediterranean region (FerroLuzzi et al, 2002).…”
Section: Discussioncontrasting
confidence: 79%
“…Our results suggest that a decrease in saturated fat should be recommended in the Catalan population. However, the 12% of energy derived from SFA found in the present study is still lower than the percentage found in other European populations (Slimani et al, 2002;Capita and Alonso-Calleja, 2003;Waijers et al, 2006) even in the Mediterranean region (FerroLuzzi et al, 2002).…”
Section: Discussioncontrasting
confidence: 79%
“…11 In some centres, additional information on caffeinated and decaffeinated coffee consumption was obtained [Germany, Greece, Italy (except Ragusa and Naples), Netherlands, and United Kingdom]. Information on tea consumption was not available in Norway.…”
Section: Assessment Of Dietmentioning
confidence: 99%
“…This resulted in a final sample size of 11,684 type 2 diabetes cases and a subcohort of 15,374 (including 730 of the diabetes cases).…”
Section: Subcohortmentioning
confidence: 99%
“…In addition, the diversity of dietary patterns in Europe leads to a wide variation in sweet beverage consumption across different countries, with a clear north-south gradient (i.e. higher consumption in northern than in southern European countries) [13,15].…”
Section: Introductionmentioning
confidence: 99%